The benefits and burden of health financing in Indonesia: analyses of nationally representative cross-sectional data. Issue 5 (May 2023) - Asante, Augustine; Cheng, Qinglu; Susilo, Dwidjo; Satrya, Aryana; Haemmerli, Manon; Fattah, Rifqi Abdul; Kosen, Soewarta; Novitasari, Danty; Puteri, Gemala Chairunnisa; Adawiyah, Eviati; Hayen, Andrew; Mills, Anne; et al.
Summary: Background: Indonesia has committed to deliver universal health coverage by 2024. Reforming the country's health-financing system is key to achieving this commitment. We aimed to evaluate how the benefits and burden of health financing are distributed across income groups and the extent to which Indonesia has achieved equity in the funding and delivery of health care after financing reforms. Methods: We conducted benefit incidence analyses (BIA) and financing incidence analyses (FIA) using cross-sectional nationally representative data from several datasets. Two waves (Feb 1 to April 30, 2018, and Aug 1 to Oct 31, 2019) of the Equity and Health Care Financing in Indonesia (ENHANCE) study household survey involving 7500 households from ten of the 34 provinces in Indonesia were used to obtain health and socioeconomic status data for the BIA. Two waves (2018 and 2019) of the National Socioeconomic Survey (SUSENAS), the most recent wave (2014) of the Indonesian Family Life Survey, and the 2017 and 2018 National Health Accounts were used to obtain data for the FIA. In the BIA, we calculated a concentration index to assess the distribution of health-care benefits (−1·0 [pro-poor] to 1·0 [pro-rich]), considering potential differences in health-care need. In the FIA, we evaluated the equity of health-financing contributions by socioeconomic quintiles by calculating the Kakwani index to assess the relative progressivity of each financing source. Both the BIA and FIA compared results from early 2018 (baseline) with results from late 2019. Findings: There were 31 864 participants in the ENHANCE survey in 2018 compared with 31 215 in 2019. Women constituted 50·5% and men constituted 49·5% of the total participants for each year. SUSENAS had 1 131 825 participants in 2018 compared with 1 204 466 in 2019. Women constituted 49·9% of the participants for each year, whereas men constituted 51·1%. The distribution of health-care benefits in the public sector was marginally pro-poor; people with low income received a greater proportion of benefits from health services than people with high income between 2018 (concentration index –0·008, 95% CI –0·075 to 0·059) and 2019 (–0·060, –0·139 to 0·019). The benefit incidence in the private health sector was significantly pro-rich in 2018 (0·134, 0·065 to 0·203, p=0·0010) and 2019 (0·190, –0·192 to 0·572, p=0·0070). Health-financing incidence changed from being moderately progressive in 2018 (Kakwani index 0·034, 95% CI 0·030 to 0·038) to mildly regressive in 2019 (–0·030, –0·034 to –0·025). Interpretation: Although Indonesia has made substantial progress in expanding health-care coverage, a lot remains to be done to improve equity in financing and spending. Improving comprehensiveness of benefits will reduce out-of-pocket spending and allocating more funding to primary care would improve access to health-care services for people with low income. Funding: UK Health Systems Research Initiative, UK Department of International Development, UK Economic and Social Research Council, UK Medical Research Council, and Wellcome Trust.